1988
DOI: 10.1128/aac.32.7.1097
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane permeation of Bacteroides fragilis by cephalosporins

Abstract: Outer membrane permeation of Bacteroides fragilis by cephalosporins was examined by a previously described method. The permeation parameters of cephalosporins in B. fragilis were close to iO-5 cm3/min per ,ug of cell dry weight. These values were about an order of magnit4de lower than those in Escherichia coli. In B. fragilis, the permeation was not directly proportional to the hydrophilicity of cephalosporins, and the ion selectivity was weak.The mechanism of action of ,B-lactam antibiotics has been studied e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…S4C ). Negatively charged stressors tested included cefsulodin (1 negative charge) ( 51 ), potassium chromate (2 negative charges), and sodium arsenate (1 or 2 negative charges; pK a , 7.03). For both chromate and arsenate, the MIC was the same for both strains regardless of the Fe(II) concentration.…”
Section: Resultsmentioning
confidence: 99%
“…S4C ). Negatively charged stressors tested included cefsulodin (1 negative charge) ( 51 ), potassium chromate (2 negative charges), and sodium arsenate (1 or 2 negative charges; pK a , 7.03). For both chromate and arsenate, the MIC was the same for both strains regardless of the Fe(II) concentration.…”
Section: Resultsmentioning
confidence: 99%
“…B. fragilis G-242 produced a large amount of P-lactamase. In a previous paper, we reported that the outer membrane permeations by the five cephalosporins in B. fragilis G-242 were nearly equal (32). There are no data concerning the affinity for PBPs in B. fragilis G-242 because…”
Section: Methodsmentioning
confidence: 98%
“…These differences may account for some cases of b-lactam resistance. In two studies, cefoxitin resistance of B. fragilis and B. thetaiotaomicron strains appeared to involve decreased affinity of the PBPs for the drug and a similar study of a cephalothin-resistant B. fragilis strain showed that both reduced permeation and PBP affinity were responsible for resistance (Piddock and Wise, 1986;Yotsuji et al, 1988b;Wexler and Halebian, 1990).…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…The Bacteroides spp. appear to have at least three high mol wt PBPs (58,000-90,000 Da) and several smaller sized PBPs as estimated by sodium dodecylsulfate polyacrylamide gel electrophoresis (SDS-PAGE; Piddock and Wise, 1986;Piddock and Wise, 1987;Yotsuji et al, 1988b;Wexler and Halebian, 1990). The high mol wt PBPs have been correlated with similar proteins in E. coli, and each Bacteroides spp.…”
Section: Mechanisms Of Resistancementioning
confidence: 99%